Short‐term biomarkers of apple consumption - Saenger, Theresa (Mol Nutr Food Res, 2016)
SCOPE: Urinary biomarkers are used to estimate the nutritional intake of humans. The aim of this study was to distinguish between low, medium, and high apple consumption by quantifying possible intake biomarkers in urine samples after apple consumption by HPLC‐MS/MS. Apples were chosen as they are the most consumed fruits in Germany. METHODS AND RESULTS: Thirty subjects took part in 7‐day study. They abstained from apples and apple products except for one weighed apple portion resembling one, two, or four apples. Before apple consumption and during the following days spot urine samples were collected. These urine samples were incubated with β‐glucuronidase, diluted, and directly measured by HPLC‐MS/MS. Phloretin, epicatechin, procyanidin B2, and quercetin were detected in urine using Scheduled MRM(TM) mode. Phloretin was confirmed as a urinary biomarker of apple intake and had the ability to discriminate between low or medium (one or two apples) and high apple consumption (four apples). The groups also differ in the excretion of epicatechin and procyanidin B2. CONCLUSION: Apple consumption can be monitored by urinary biomarkers for a period of at least 12 h after consumption. Furthermore the amount of apples consumed can be estimated by the concentration of certain biomarkers.